2003
DOI: 10.1002/art.11199
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of primary sjögren's syndrome with low‐dose human interferon alfa administered by the oromucosal route: Combined phase III results

Abstract: Objective. This study tested the safety and efficacy of human interferon (IFN) alfa for treatment of salivary hypofunction and dry mouth symptoms in primary Sjö gren's syndrome patients. Methods. Combined results are reported from 2 phase III clinical trials in which a total of 497 subjects with primary Sjö gren's syndrome received 150 international units of human IFN alfa or matching placebo 3 times per day for 24 weeks by the oromucosal route. Results. Subjects given IFN alfa had a significantly (P ‫؍‬ 0.01)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0
9

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(65 citation statements)
references
References 43 publications
1
55
0
9
Order By: Relevance
“…Low dose administration of IFN- is defined as IFN- administration with the amount of 0.05-1000 IU/kg, compared to high dose administration of IFN-, which is one of the traditional treatments by intramuscular or subcutaneous injection applied to hepatitis C, uses several hundreds to ten million IU/kg [39]. Human IFN- (HuIFN-) has been given orally in low doses to treat or prevent a number of infectious and immune-based diseases in a variety of species [2,7,14,26]. Notably, the oral administration of natural HuIFN- has been shown to be therapeutic in respiratory tract infections in cattle [6,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low dose administration of IFN- is defined as IFN- administration with the amount of 0.05-1000 IU/kg, compared to high dose administration of IFN-, which is one of the traditional treatments by intramuscular or subcutaneous injection applied to hepatitis C, uses several hundreds to ten million IU/kg [39]. Human IFN- (HuIFN-) has been given orally in low doses to treat or prevent a number of infectious and immune-based diseases in a variety of species [2,7,14,26]. Notably, the oral administration of natural HuIFN- has been shown to be therapeutic in respiratory tract infections in cattle [6,13].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that low dose oral administration (LDOA) of type I IFN is effective against chronic diseases and infectious diseases [2,6,7,13,14]. The mechanism of systemic immune response regulation by LDOA of IFN- is suggested as humoral or cellmediated via mucosal epithelial cells [5,11,37,38,41].…”
mentioning
confidence: 99%
“…In one large double-blinded, placebo-controlled randomized controlled trial, interferon alpha was given via oromucosal route. Unfortunately, the drug failed to show benefit in reducing oral dryness and stimulated salivary flow [29].…”
Section: Novel Biological Therapies For Primary Sjogren's Syndromementioning
confidence: 99%
“…Besides antiviral effects, IFN- has immunomodulating properties. Four pilot studies have shown beneficial effects of oromucosal IFN-, whereby salivary flow was increased and salivary gland histology after treatment demonstrated reduced lymphocytic infiltrâtes (Cummins et al, 2003;Tobon et al, 2010). A phase III trial performed later, showed an increase in unstimulated salivary flow but the main clinical endpoint, which was improvement of stimulated salivary flow, was not met.…”
Section: Inhibition Of Ifn Releasementioning
confidence: 99%